The Role of PAUD Teachers in Implementing The Holistic Environment Based on Children's Health, Nutrition and Safety - Dewi Sagala, Anita Chandra; Pusari, Ratna Wahyu; Karmila, Mila (Indonesian Journal of Early Childhood Education Studies, 2018)
The aim of this study is to describe the role of the teacher in creating an atmosphere that provides a good environment for children’s health, nutrition and safety. The teachers must be able to provide a protection during teaching and learning in schools by creating a healthy environment and awareness of the importance of nutrition, health and safety in children development. To complete this task, the teacher must focus on three basic areas: security, health and nutrition for children. The PAUD teachers integrate health, safety, and nutrition into the curriculum. This means that the teacher includes this program every day. This research was conducted in 2017 at Daqu School Semarang. The research methodology used naturalistic qualitative. The result is the role of the teacher in preparing a holistic environment including: (1) minimizing the risk of children's health, nutrition and safety, (2) utilizing education as tool of heath promotion and reducing the risk for children and parents, (3) understanding the importance of guidelines, standards, and laws for children's health, nutrition and safety, (4) practicing the culture competence, (5) developing partnership with family for giving a concern to the society.